Changes in Polish Foreign Trade of Cattle Livestock and Beef - Bąk-Filipek, Ewa (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The main objective of the study was to analyse the changes and the conditions of foreign traded beef. The economic and political situation has had an impact on Poland’s foreign trade of agricultural food products. The main factors affecting international trade, and which have significantly decreased the growth rate of exports and imports of animal products, are the following: decreased oil prices and exchange rate fluctuations, uncertainties related to the conflict in Ukraine, restrictions in trade with Russia, destabilisation in the Middle East and concerns about the future of the euro zone.